A Balance between Inhibitor Binding and Substrate Processing Confers Influenza Drug Resistance. Issue 3 (13th February 2016) - Jiang, Li; Liu, Ping; Bank, Claudia; Renzette, Nicholas; Prachanronarong, Kristina; Yilmaz, Lutfu S.; Caffrey, Daniel R.; Zeldovich, Konstantin B.; Schiffer, Celia A.; Kowalik, Timothy F.; Jensen, Jeffrey D.; Finberg, Robert W.; et al.
Abstract: The therapeutic benefits of the neuraminidase (NA) inhibitor oseltamivir are dampened by the emergence of drug resistance mutations in influenza A virus (IAV). To investigate the mechanistic features that underlie resistance, we developed an approach to quantify the effects of all possible single-nucleotide substitutions introduced into important regions of NA. We determined the experimental fitness effects of 450 nucleotide mutations encoding positions both surrounding the active site and at more distant sites in an N1 strain of IAV in the presence and absence of oseltamivir. NA mutations previously known to confer oseltamivir resistance in N1 strains, including H275Y and N295S, were adaptive in the presence of drug, indicating that our experimental system captured salient features of real-world selection pressures acting on NA. We identified mutations, including several at position 223, that reduce the apparent affinity for oseltamivir in vitro . Position 223 of NA is located adjacent to a hydrophobic portion of oseltamivir that is chemically distinct from the substrate, making it a hotspot for substitutions that preferentially impact drug binding relative to substrate processing. Furthermore, two NA mutations, K221N and Y276F, each reduce susceptibility to oseltamivir by increasing NA activity without altering drug binding. These results indicate that competitive expansion of IAV in the face of drug pressure is mediated by a balance between inhibitor binding and substrate processing. Graphical abstract: Highlights: Limited influenza mutants have been examined for fitness costs and drug resistance. Fitness effects in critical regions of N1 NA were quantified by EMPIRIC ( E xceedingly M eticulous and P arallel I nvestigation of R andomized I ndividual C odons). Many mutations exhibited increased fitness in the presence of oseltamivir. NA position 223 is a hotspot for mutations that decrease binding to oseltamivir. Drug resistance results from a balance of drug binding and substrate processing.